Trophic Transfer and Accumulation of Microplastics in Freshwater Ecosystem: Risk to Food Security and Human Health - Nair, Haritha Thulaseedharan; Perumal, Siddhuraju (International Journal of Ecology, 2022)
Plastic pollution is not at all a novel matter to the scientific as well as the public community. However, the knowledge of the general public when it comes to microplastic pollution is still in its infancy. The major sources of these tiny plastic particles in the aquatic environment are laundry, abrasion of household plastics, cosmetics, personal care products, tyre wear, food wrappings, and so on. However, the public is not much aware that they are part of these major emission sources and how much they are contributing to it. Also, the vast majority of research conducted to date on plastic pollution in all size fractions has focused more on marine ecosystems than freshwater ecosystems. Hence, people are more associated with freshwater ecosystems than marine ecosystems; it should be given additional importance.Rather than the effect on aquatic organisms through ingestion and other ways, the ecological risks posed by micro and nanoplastics as vectors for chemical contaminants and their accumulation through trophic transfer are more serious and of utmost importance. Aquatic life or aquatic ecosystem is already affected by a multitude of environmental stressors, and now microplastics and nanoplastics may represent a significant additional risk to food security. Micro and nanoplastics have already invaded our diet in various ways. Even if it does not show any immediate effect on human health, long-term exposure may pose a serious threat to the human population. Hence, identifying the possible sources and reducing exposure to these sources is of utmost importance.